Routledge encyclopedia of international political economy - Jones, R.J. Barry (Routledge, 2001)
This encyclopedia offers a comprehensive and authoritative survey of the rapidly developing field of international political economy. Its entries provide a guide to the basic issues, concepts, and institutions used by international political economy in its various forms.